Modelagem computacional de cultura de células tumorais em dispositivos de microfluídica utilizando o método dos elementos finitos - Bonifácio, Elton Diêgo (2023)
Despite advances in biomedical sciences, cancer remains one of the leading causes of death in the world. Complex interactions between tumor cells and their microenvironment contribute to tumor initiation and progression in addition to the development of drug-resistant tumor cells. The tumor microenvironment (TM) is heterogeneous and highly complex consisting of a spatial-temporal variation of nutrients, mechanical signals, among others, which influence several cellular processes such as proliferation, differentiation and migration. Modeling TM conditions in vitro with this complexity is technically a challenge. Traditional animal cancer models and in vitro cancer models are limited in their ability to recapitulate human structures and functions, thus hindering appropriate therapeutic strategies. In this context, recent advances in microfluidic technology have offered opportunities to mimetize a physiologically relevant TM found by tumor cells in vivo. The development and application of microfluidic cancer models have the potential to overcome some of the limitations inherent to traditional models. Moreover, the possibility of computationally modeling microchips intended for biological analysis represents an advance in the study of cellular behavior. Currently, there is no model focused on the study of tumor cell cultures in microfluidic devices that contemplates the behavior of cells due to the availability of glucose, oxygen and pH of TM. Therefore, the main objective of this work is the development of computational mathematical models that simulate aspects of tumor cell behavior, such as proliferation and death, inside a microfluidic device, depending on the conditions of TM using the finite element method. For this, models were implemented to evaluate the space-time pattern of nutrients inside a microchip as a function of some physical parameters and material properties that usually vary in experiments. Then, a mathematical model was developed that includes the influence of glucose, oxygen, microchip dimensions and production of metabolic residues on tumor cell behavior. Different case studies were evaluated considering the variation of the initial density of cells, regime of renewal of the culture medium, variation of chip geometry, among others. The results showed a good agreement with experimental observations reported in the literature that present the formation of the necrotic nucleus due to nutrient scarcity and TM acidity, especially for conditions of high initial cell density. The models proposed in this work allow us to evaluate how the distribution of glucose, oxygen and H+ ions occurs inside a microfluidic device and how these influence the behavior of cell proliferation and death. Therefore, these models are tools that can help in experimental planning involving microfluidic systems, since they allow analyzing a wide variety of biological experiments without the difficulties of time and consumption of reagents inherent to experimental investigations.